Cantom, volume 3 ebook Tales of the unnamed world canto and the city of giants. - Booher, David M. (Canto, 2024)
A tiny clockwork hero on a quest for a heart continues fighting for love, freedom, and hope, gathering allies to face tyrannical forces in a fantastical modern fairytale.Still on the mend following his first confrontation with the Shrouded Man, Canto must search for allies to stand by his side in their inevitable final battle. And who could ask for better allies than the fearsome Giants? But to earn their allegiance, he’ll need to solve the Labyrinth outside their city and slay the monster that lurks at its heart!Then, Canto and his friends must cross a bridge guarded by a mysterious bard. The price to pass? A story never heard in all the world!Series co-creators David M. Booher and Drew Zucker are joined by Sebastián Píriz, Liana Kangas, Jorge Corona, and Shawn Daley for a special installment of Canto’s “striking modern fairy tale” (Newsarama). Bridging the events of Canto: The Hollow Men and Canto: Lionhearted, this swashbuckling, uplifting volume collects Canto and the City of Giants and both issues of Canto: Tales of the Unnamed World in a high-quality hardcover reprint with a brand new cover.